2016
DOI: 10.1017/s0022215116008665
|View full text |Cite
|
Sign up to set email alerts
|

A survey of ENT experience in South West Peninsula general practitioner trainees: how can post-graduate ENT training be improved?

Abstract: Further ENT training is required for doctors in general practitioner training schemes to aid improvement of patient care. The most logical way to enhance ENT training in a post-graduate setting is through up-to-date courses held locally with a faculty made up of experts working within the specialty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…It has been long recognised that GPs receive limited ENT training at both undergraduate and postgraduate level16 and this is particularly important in light of the number of ENT conditions that are initially seen in general practice. Our findings agree with previous research that GPs would like further ENT training,17 and that regional courses and updates might be useful to improve knowledge, clinical skills and referral pathways to secondary care.…”
Section: Discussionsupporting
confidence: 92%
“…It has been long recognised that GPs receive limited ENT training at both undergraduate and postgraduate level16 and this is particularly important in light of the number of ENT conditions that are initially seen in general practice. Our findings agree with previous research that GPs would like further ENT training,17 and that regional courses and updates might be useful to improve knowledge, clinical skills and referral pathways to secondary care.…”
Section: Discussionsupporting
confidence: 92%
“…15 Likewise, 57% of general practitioner trainees in the UK reported 1 week or less of OHNS exposure during their undergraduate training. 5 In a Canadian survey, the majority of residents expressed inadequate OHNS training in UME with “very little” classroom (57%) and clinical instruction (63%). 16…”
Section: Introductionmentioning
confidence: 99%
“…1 Yet, studies from around the world consistently find otolaryngology—head and neck surgery (OHNS) to be underrepresented in undergraduate medical curricula. 2-7…”
Section: Introductionmentioning
confidence: 99%
“…An online general practitioner trainee survey conducted by Easto and Reddy, with a response rate of 60.5 per cent, found that nearly 60 per cent of general practitioner trainees spent no time in ENT posts in post-graduate training, and 65 per cent of general practitioner trainees received no formal ENT teaching after medical school. 3 However, 93.4 per cent of trainees were keen to attend a 1-day ENT course if provided locally. Locally available courses for general practitioner trainees made up of local experts is therefore encouraged, especially given that within primary care 15-20 per cent of adult presentations and up to 50 per cent of paediatric presentations are ENT-related.…”
mentioning
confidence: 99%
“…ENT training is currently a topical issue. An online general practitioner trainee survey conducted by Easto and Reddy, with a response rate of 60.5 per cent, found that nearly 60 per cent of general practitioner trainees spent no time in ENT posts in post-graduate training, and 65 per cent of general practitioner trainees received no formal ENT teaching after medical school 3 . However, 93.4 per cent of trainees were keen to attend a 1-day ENT course if provided locally.…”
mentioning
confidence: 99%